Cost of close the gap for vision of Indigenous Australians: On estimating the extra resources required. (December 2013) - Hsueh, Ya‐seng (Arthur); Brando, Alex; Dunt, David; Anjou, Mitchell D.; Boudville, Andrea; Taylor, Hugh
Abstract Objective To estimate the costs of the extra resources required to close the gap of vision between Indigenous and non‐Indigenous Australians. Design Constructing comprehensive eye care pathways for Indigenous Australians with their related probabilities, to capture full eye care usage compared with current usage rate for cataract surgery, refractive error and diabetic retinopathy using the best available data. Setting Urban and remote regions of Australia. Interventions The provision of eye care for cataract surgery, refractive error and diabetic retinopathy. Main outcome measures Estimated cost needed for full access, estimated current spending and estimated extra cost required to close the gaps of cataract surgery, refractive error and diabetic retinopathy for Indigenous Australians. Results Total cost needed for full coverage of all three major eye conditions is $45.5 million per year in 2011 Australian dollars. Current annual spending is $17.4 million. Additional yearly cost required to close the gap of vision is $28 million. This includes extra‐capped funds of $3 million from the Commonwealth Government and $2 million from the State and Territory Governments. Additional coordination costs per year are $13.3 million. Conclusions Although available data are limited, this study has produced the first estimates that are indicative of the need for planning and provide equity in eye care.